The impact of COVID-19 on consumption poverty in Mozambique - Giulia Barletta; Finório Castigo; Eva-Maria Egger; Michael Keller; Vincenzo Salvucci; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study assesses the impact of the COVID-19 pandemic and the state of emergency implemented by the Government of Mozambique on household consumption poverty. To predict changes in income and the associated effects on poverty and inequality, we rely on macroeconomic impacts estimated by Betho et al. (2021) using a social accounting multiplier model. We assume two main impact channels are at work leading to higher consumption poverty: direct income/wage and employment losses. To estimate the direct income/wage losses, we use the information from Betho et al. (2021) on the impact on wages, on gross domestic product by industry, and on household income; to estimate the employment losses, we use the information on the impact on employment from Betho et al. (2021). The two impact channels are then combined to assess the final impact on consumption and poverty. Our simulations suggest that consumption decreased by between 7.1 and 14.4 per cent, and that poverty increased by between 4.3 and 9.9 percentage points in 2020, depending on the specification. This corresponds to about 2 million people entering poverty in less than a year and to a reversal of the positive poverty reduction trend observed during the period 2008/09-2014/15. While the COVID-19 shock affected urban areas the most, our results indicate that rural areas experienced a higher increase in poverty rates due to the already low levels of consumption. Poverty most certainly increased in the pre-COVID 2015- 20 period due to other shocks, so Mozambique finds itself in an intense and deepening struggle against poverty.
Keywords: I32; O21; 330; COVID-19; poverty; inequality; Mozambique